Linear Decision Rules for Economic Stabilization and Growth: Comment - Holmes, W. Lynn (Quarterly Journal of Economics, 1968)
Journal Article Linear Decision Rules for Economic Stabilization and Growth: Comment Get access W. Lynn Holmes W. Lynn Holmes Temple University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 82, Issue 3, August 1968, Pages 514–518, https://doi.org/10.2307/1879524 Published: 01 August 1968